Diversidade de bactérias de solo sob vegetação natural e cultivo de hortaliças - Val-Moraes, Silvana Pompeia [UNESP]; Valarini, Maria Jose; Ghini, Raquel; de Macedo Lemos, Eliana Gertrudes; Carareto-Alves, Lucia Maria [UNESP] (Univ Federal Ceara, Dept Geol, 2009)
The microorganisms are essential components in the maintenance of the biological and physicochemical balance of the soil. They exert important function including the degradation of residues of plants and animals and the release of nutrients in the alimentary chain. This work had as objective to compare the microbiota of a soil under bush covering (SMS) and other cropped with vegetables (SHC), suppressive or not it Rhizoctonia solani. Total microbial community DNA was extracted of soils, amplification for PCR of the genes 16S rDNA, inserted into pGEM (R)-T cloning vector and sequencing of the genes of the ribosomal RNA. The analysis of the results demonstrated that this methodology was efficient for evaluation of bacteria in ground. In the bush soil suppressive the microorganisms more found belonged to the phyla of the Acidobacterias, Verrucomicrobia and Actinobacterias and in the soil cultivated with vegetables the biggest frequency was of organisms pertaining to the phyla of the Proteobacterias, Firmicutes and Bacteroidetes.
Diversity of bacteria of the soil under natural vegetation and vegetables cropping
Keywords: Conducive soil; Suppressive soil; Metagenome; Rhizoctonia solani